The velocity of temporalis muscle wasting in cerebral metastasis is prognostic for poor survival - Rafaelian, Artem; Won, Sae-Yeon; Behmanesh, Bedjan; Cantré, Daniel; Bernstock, Joshua D.; Freiman, Thomas M.; Seidlitz, Jakob; Baumgarten, Peter; Dinc, Nazife; Konczalla, Juergen; Gessler, Florian; Dubinski, Daniel (Frontiers in Oncology, 2025)
PurposeRecently, the temporalis muscle thickness on cranial CT scan was proposed as a surrogate marker for patients’ baseline frailty that correlates with outcome in primary and metastatic brain tumor patients. In this study, we investigated whether the velocity of temporalis muscle atrophy (TMA) affects the outcome of patients with cerebral metastases.MethodsWe analyzed radiological and clinical data sets of 96 patients who received craniotomy for cerebral metastasis resection in our institution. We then correlated the radiological data with clinical course and outcome after stratification for the velocity of temporalis muscle atrophy.ResultsThe median velocity of TMA was 0.0016 mm/day. In patients with a slow TMA rate, the median overall survival was significantly longer than in patients with a fast TMA rate (37.7 months versus 22.9, p = 0.0007). Furthermore, patients with slow TMA had longer progression-free survival postoperatively (7.6 versus 4.38 months, p <0.0001). The overall survival postoperatively (OS-PO) was also significantly longer in patients with slow TMA (8.9 months versus 5.1, p=0002).ConclusionBased on this study, the velocity of temporalis muscle atrophy may represent an objective and dynamic index with potential for survival prognostication for patients with cerebral metastases.